Open Education and Second Language Learning and Teaching : The Rise of a New Knowledge Ecology - Carl S. Blyth; Joshua J. Thoms (Multilingual Matters, 2021)
Compared with STEM fields, foreign language (FL) education and second language acquisition have only slowly embraced open education and the new knowledge ecologies it produces. FL educators may have been hesitant to participate in the open education movement due to a lack of research which investigates the benefits and challenges of FL learning and teaching in open environments. This book contextualizes open education in FL learning and teaching via an historical overview of the movement, along with an in-depth exploration of how the open movement affects FL education beyond the classroom context; fills the research void by exploring aspects of open second language learning and teaching across a range of educational contexts; and illustrates new ways of creating, adapting and curating FL materials that are freely shared among FL educators and students. This book is open access under a CC BY ND licence.